A critical analysis of the impact of water on the South African campaign in German South West Africa, 1914-1915 (Historia, 2021)
The South African campaign in German South West Africa (GSWA) during the First World War depended largely on the access, availability and control of all water sources in the operational area. The Union Defence Force (UDF) appreciated the strategic nature of water before the invasion of GSWA in 1914, because it was well known that there were no permanent water sources along the routes of advance into the country. Fears about the possibility of German sabotage and poisoning of the available water remained a constant concern for the South African defence planners throughout the campaign, and adequate water supplies that were fit for both human and animal consumption became a strategic military concern. This meant that the Defence Force had to adopt a number of measures to meet the growing demand for water. Boreholes were sunk across the operational area and in addition, fresh water was transported across the Kalahari Desert by motor vehicles and via shipping from Cape Town. To some extent, the provision of safe drinking water dictated the pace of the South African campaign in GSWA.
Keywords: First World War; German South West Africa; Union Defence Force; offensive operations; climate and terrain; water